Tobaccolympics: Faster, higher, stronger and even smokier... - Abd Razak, Dzulkifli (1996)
TOMORROW, THE ATLANTA OLYMPIC will be over. Many new worldclass standards have been set in the past 2 weeks or so. In this sense Malaysia too has set a new Olympic records. Malaysians should take pride in any medals won by our athletes. If we managed only a bronze in the last Olympics, In Atlanta, at least we did better. However, while we celebrate this achievement, we cannot overlook certain things that have not changed. Much like the previous Olympics, we have been subjected to such intense "indirect" tobacco advertisements. The difference, this time perhaps lies in the theme "Breakaway." Youngster have taken to the tune of the theme quite naturally. One wonders whether they will take that extra step to smoke the brand of cigarette implied in the advertisements. The association between the ad and the games is of course, a positive one. It climaxed with an archer lighting the symbolic Olympic touch supported by the advertiser's logo. Talk about positive reinforcement. Moreover, there was not a single reminder during the period stating that smoking is hazardous to health or at least incomparable with sports.